Assessment of Metarhizium anisopliae (Metchnikoff) from natural forest to control tiger moth Atteva sciodoxa (Meyrick) - Wan Azhar, Wan Muhammad Azrul (2017)
Eurycoma longifolia or ‘tongkat ali’ is a well-known tropical medicinal plant used widely to cure human illness. However, this plant is highly vulnerable to several insect pests, especially Atteva sciodoxa larvae. In the present study, a total of 28 E. longifolia forest and cultivation areas in Peninsular Malaysia were surveyed. Results of the surveys showed that A. sciodoxa larvae infestation was major and common in E. longifolia’s plantations, followed by scale insect, Zeuzera stem borer, animal damage, Coptotermes sp. and spider mites. Several diseases were also observed such as algal leaf spots, sooty mould, Sudden Death Syndrome (SDS) and Colletotrichum leaf spot. Twenty five Metarhizium anisopliae isolates obtained from natural forest soils of Peninsular Malaysia were identified and screened for pathogenicity against A. sciodoxa larvae. Morphology of the fungus was studied and a phylogenetic tree of the fungal ITS region sequences was developed. The study revealed that cultures of the fungal isolates were flat with a yellowish mycelial mat bearing brownish to dark green masses of conidia. Conidia were single celled, cylindrical with rounded tips and varied in size, ranging from 5.7 ± 0.5μm × 2.5 ± 0.4 μm to 7.4 ± 1.0 μm × 3.3 ± 1.0 μm. They were then identified as M. anisopliae var. anisopliae due to short shaped conidia. Phylogenetic analysis found that all the isolates were closely related within species regardless of their geographic origins. The species was also found to be closely related with M. anisopliae var. majus supported with 99% bootstrap value. Growth rate test showed that SDA is a media supported fastest fungus growth followed by PDA, MEA, CMA and WA at temperatures 25oC, 28 oC and 31 oC. Screening tests revealed that all the isolates were pathogenic against the inoculated A. sciodoxa larvae with mortality as early as 3 days after inoculation. The highest larval mortality recorded by FRIM858, followed by FRIM880, FRIM873, FRIM859, FRIM862, FRIM871 and the least virulent was FRIM878. None of the larvae in the inoculated control treatment died. Further study was conducted on isolates FRIM880, FRIM871, FRIM859 and FRIM858 to determine the median effective conidia concentration (EC50) and median effective time (ET50) against the pest larvae. The study revealed that FRIM589 was the most effective and aggressive against the pest larvae. The EC50 recorded was 1.1x106 conidia ml-1 and ET50 was 2.9 days. Field trials in KESEDAR Gua Musang and Sg. Menyala Forest Reserve show that FRIM859 significantly reduce population of A. sciodoxa larvae with 57.0% and 63.4% larvae reduction, respectively. The study suggests that FRIM589 was the best candidate to be developed as biological control agent against A. sciodoxa larvae.